Metabolismo do ácido 7- 14c - 2,3,5 triiodo benzóico (TIBA) em soja (Glycine max) - Sant’Anna, R; Ohlrogge , A J; Christian , J E (Revista Ceres, 2025)
A metabolic study was done in mature seeds of field grown soybeans sprayed with 7 - 14C - 2,3,5 triiodobenzoic acid (TIBA) at the onset of flowering. Seed extraction with 95% alcohol yielded only 65% of the total radioactivity present. No further studies were performed on the ethanol insoluble fraction. Upon acid base purification of the 14C seed extracts, the ether phase (pH 9,0) contained about 70% of the activity suggesting the existence of a low polarity compound(s). Acid hydrolysis of the alcoholic extracts increased the radioactivity in the ether soluble fraction, while the basic treatment decreased it to about the same level as for free TIBA.